Hepatitis C virus coinfection independently increases the risk of cardiovascular disease in HIV‐positive patients. Issue 1 (21st September 2015) - Fernández‐Montero, J. V.; Barreiro, P.; de Mendoza, C.; Labarga, P.; Soriano, V.
Summary: Patients infected with HIV are at increased risk for cardiovascular disease despite successful antiretroviral therapy. Likewise, chronic hepatitis C virus (HCV) infection is associated with extrahepatic complications, including cardiovascular disease. However the risk of cardiovascular disease has not been formally examined in HIV/HCV‐coinfected patients. A retrospective study was carried out to assess the influence of HCV coinfection on the risk of cardiovascular events in a large cohort of HIV‐infected patients recruited since year 2004. A composite event of cardiovascular disease was used as an endpoint, including myocardial infarction, angina pectoris, stroke or death due to any of them. A total of 1136 patients (567 HIV‐monoinfected, 70 HCV‐monoinfected and 499 HIV/HCV‐coinfected) were analysed. Mean age was 42.7 years, 79% were males, and 46% were former injection drug users. Over a mean follow‐up of 79.4 ± 21 months, 3 patients died due to cardiovascular disease, whereas 29 suffered a first episode of coronary ischaemia or stroke. HIV/HCV‐coinfected patients had a greater incidence of cardiovascular disease events and/or death than HIV‐monoinfected individuals (4% vs 1.2%, P = 0.004) and HCV‐monoinfected persons (4% vs 1.4%, P = 0.5). After adjusting for demographics, virological parameters and classical cardiovascular disease risk factors (smoking, hypertension, diabetes, high LDL cholesterol), both HIV/HCV coinfection (HR 2.91; CI 95%: 1.19–7.12; P = 0.02) and hypertension (HR 3.65; CI 95%: 1.34–9.94; P = 0.01) were independently associated with cardiovascular disease events and/or death in HIV‐infected patients. Chronic hepatitis C and hypertension are independently associated with increased cardiovascular disease risk in HIV‐infected patients. Therefore, treatment of chronic hepatitis C should be prioritized in HIV/HCV‐coinfected patients regardless of any liver fibrosis staging.